Microbial effects - Paul, Eldor A., author; Hardy, Ralph W. F., author; Lamborg, Marvin R., author; AAAS, publisher (Colorado State University. Libraries, 1983)
The recommendations for microbiological research needs are based on the following general scenario: a) increased atmospheric CO2 will increase crop productivities by 10-40%, depending on crop and geographic area, which in turn will increase biomass and soil organic matter by 5-40%; b) additional root-derived materials and crop residue in the soil will increase soil microbial activities, producing a greater flux in most major cycles and possibly some changes in pool sizes of -10% to +30%; c) these effects will increase biological Nz fixation, and the increased demand for N will place significant limitations on phosphorus and other mineral nutrients; d) no significant changes will occur in soil O2 or CO2. The postulated doubling of atmospheric CO2 is not likely to have a direct effect on soil microbial activity because during the growing season, the concentration of CO2 in the soil atmosphere is already ten to fifty times higher than existing atmospheric CO2. Based on all available experimental information, it is estimated that a doubling of atmospheric CO2 will cause an increase in primary productivity of ten to forty percent, depending on locale. The increase in biomass will, in turn, produce a limitation of available soil nutrients, especially nitrogen and phosphorus. Increased organic carbon together with nitrogen and/or phosphorus limitation will result in a preferential increase in nitrogen fixation and mycorrhizal activities as the expedient means for supplying required nutrients to sustain the predicted increase in primary productivity. Therefore, increased emphasis should be placed on fundamental research related to soil microbiology with special reference to nitrogen-fixing, nitrifying and denitrifying bacteria, and to the mycorrhizal fungi.